The analysis of the histomorphometric characteristics and ultrastructural features of the liver in response to environmental cycle desynchronization in the wild desert rodent (Gerbillus tarabuli) - Derbouz Rouibate, Amina; Benhafri, Nadir; Ouali-Hassenaoui, Saliha; Dekar- Madoui, Aicha (Acta Biologica Szegediensis, 2024)
The architecture of the hepatic tissue in the nocturnal wild desert rodent (Gerbillus tarabuli) subjected to a shifted LD (Light/Dark) cycle was investigated using transmission electron microscopy and histomorphometry. Investigation involved two groups: the control group (n = 5), exposed to the regular LD cycle (LD: 12:12), and the shifted group (n = 5), exposed to the LD regimen with a prolonged light phase of 8 h, in a day by day alternation with regular LD cycle (LD: 12:12 / LD: 20:4) during 12 weeks. Histological examination showed in the shifted group disorganization of hepatocyte trabeculae, sinusoidal dilatation, and inflammatory cell infiltration around the portal tracts. Morphometric results revealed hypertrophy of hepatocytes with a size of 29.83 ± 1.69 μm vs. 17.52 ± 0.81 μm and of their nuclei diameter with 8.69 ± 0.25 μm vs. 6.55 ± 0.15 μm. This increase is highly significant (p<0.001) and represents an increase of 70.17% and 32.67%, respectively. We also noticed a significant increase in the number of binucleated cells compared to the control group with an average of 9.73 ± 0.98 vs. 5.53 ± 0.38 binucleated hepatocytes per area unit, respectively. Ultrastructural analysis corroborated the histological findings, confirming the installation of inflammatory foci, characterized by portal and intraparenchymal infiltration of leukocytes, proliferation of Kupffer cells and stellate cells, as well as an expansion of collagen fiber deposits. Electron microscopy also revealed in the shifted group some hepatocytic lesional features represented by vacuolar or liquefied cytoplasm associated with degenerative mitochondria and a rarefaction of organelles in addition to an abundance of lysosomes. Additionally, strong glycogen depletion was observed at the metabolic level. This study showed that 12 weeks of lengthening the light phase of the LD cycle, corresponding to the gerbil's resting period, had a discernible impact on hepatocellular activity, making G. tarabuli an interesting model to study the influence of artificial light at night as a circadian rhythm disruptor.